EDIBLE FILM BERBASIS TEPUNG PORANG: TINJAUAN SISTEMATIS - Metta Sadhana, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Edible film made from porang has gained attention as a sustainable and innovative solution to reduce plastic waste and enhance food preservation. Porang, a root vegetable rich in glucomannan, is processed to create a gel-like substance that can be formed into various packaging materials. This systematic review aims to summarize the potential benefits of edible packaging made from porang. The PRISMA guideline is the method that is used to evaluate the articles that were used in this systematic review. In this systematic review, potential databases that might be used are Elsevier, Google Scholar, Pubmed, Garuda. The keywords that can be used are edible packaging, porang, plastic waste, biodegradable